Analisis Portofolio Optimal pada Saham Perbankan - Abdul Manap (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
The purpose of research is to determine how much influence the optimal portfolio according to risk and stock profit. This study uses a quantitative method with a descriptive approach, using The IDX Composite (IHSG), interest rate of Bank Indonesia Certificate (SBI), and stock price index of banking sector during August-October 2020, establishment of optimal portfolio is analyzed with single index model. The result show from 35 stocks analysed, there are 9 stocks identified as optimal portfolio with 0.3649% return and 1.0055% risk